Tuberculosis Treatment Using a Religious Approach - Solihin, Olih; Lubis, Djuara P; Muljono, Pudji Hasta; Amanah, Siti (Global Medical & Health Communication (GMHC), 2024)
In 2020, Bandung city ranked second in West Java for tuberculosis (TB) cases. The city government and stakeholders have taken health education, early detection, free treatment, and surveillance measures to address TB. Yet, a comprehensive approach is still needed. Despite previous studies exploring TB management, the role of religious approaches still needs to be explored. Employing a qualitative approach through a case study method, this research involves data collection through observation, in-depth interviews, and literature reviews. Participants are TB healthcare workers and religious speakers in Universitas ‘Aisyiyah Bandung city. In 2020, Bandung reported 8,504 TB cases with increased detection success. ‘Aisyiyah TB Care uses a religious approach to offer emotional and spiritual support to patients facing physical challenges, emotional burdens, and stigma. Religious perspectives introduce spiritual support via Islamic teachings emphasizing hygiene and self-care. Interviews reveal changed patient perceptions due to the religious approach. ‘Aisyiyah addresses TB complexity and stigma, conducting educational efforts to reshape perceptions. The religious approach assists TB sufferers, aiming for positive influence, improved relationships, and fostering hope, gratitude, and trust in God. Collaborative efforts among health, religious, and government organizations are essential for effective TB management. The research highlights the positive impact of ‘Aisyiyah TB Care's religious approach on management, addressing stigma, and enhancing well-being. Improved information dissemination and support are vital, particularly in areas with high TB burdens.